Understanding Body Language Does Not Require Matching the Body's Egocentric Map to Body Posture: A Brain Activation fMRI Study. Issue 1 (February 2020) - Canderan, Cinzia; Maieron, Marta; Fabbro, Franco; Tomasino, Barbara
Body language (BL) is a type of nonverbal communication in which the body communicates the message. We contrasted participants' cognitive processing of body representations or meanings versus body positions. Participants ( N  = 20) were shown pictures depicting body postures and were instructed to focus on their meaning (BL) or on the position of a body part relative to the position of another part (body structural description [BSD]). We examined activation in brain areas related to the two types of body representation—body schema and BSD—as modulated by the two tasks. We presumed that if understanding BL triggers embodiment of body posture, a matching procedure between the egocentric map coding the position of one's body segments in space and time should occur. We found that BL (vs. BSD) differentially activated the angular gyrus bilaterally, the anterior middle temporal gyrus, the temporal pole, and the right superior temporal gyrus, the inferior frontal gyrus, the superior medial gyrus, and the left superior frontal gyrus. BSD (vs. BL) differentially activated the superior parietal lobule (Area 7A) bilaterally, the posterior inferior temporal gyrus, the middle frontal gyrus, and the left precentral gyrus. Sensorimotor areas were differentially activated by BSD when compared with BL. Inclusive masking showed significant voxels in the superior colliculus and pulvinar, fusiform gyrus, inferior temporal gyrus, superior temporal gyrus, the intraparietal sulcus bilaterally, inferior frontal gyrus bilaterally, and precentral gyrus. These results indicate common brain networks for processing BL and BSD, for which some areas show differentially stronger or weaker processing of one task or the other, with the precuneus and the superior parietal lobule, the intraparietal sulcus, and sensorimotor areas most related to the BSD as activated by the BSD task. In contrast, the parietal operculum, an area related to the body schema, a representation crucial during embodiment of body postures, was not activated for implicit masking or for the differential contrasts.